The implications and purpose of using international phonetic symbols and English advertising slogans in advertisements in Poland - Dziczek-Karlikowska, Hanna (Scripta Neophilologica Posnaniensia, 2019)
This paper examines the various implications resulting from the use of English phonetic transcription in advertising in Poland. I focus on the problem of the use of phonetic transcription by copywriters as a graphic form and I make an attempt at showing that this technique can have pedagogical consequences, because a graphic form in which phonetic symbols are used is, in fact, a text message, not an image only. In addition, I analyze selected advertisements as a means of communication addressed to a specific recipient. In this case, I demonstrate that the use of advertising slogans in English and English phonetic transcription in Poland, does not guarantee that such advertising is effective.